2016
DOI: 10.1016/j.clim.2016.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

Klinefelter's syndrome (47,XXY) is in excess among men with Sjögren's syndrome

Abstract: Primary Sjögren's syndrome (pSS) has a strong female bias. We evaluated an X chromosome dose effect by analyzing 47,XXY (Klinefelter's syndrome, 1 in 500 live male births) among subjects with pSS. 47,XXY was determined by examination of fluorescence intensity of single nucleotide polymorphisms from the X and Y chromosomes. Among 136 pSS men there were 4 with 47,XXY. This was significantly different from healthy controls (1 of 1254 had 47,XXY, p=0.0012 by Fisher's exact test) as well men with rheumatoid arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…The effect of incomplete X inactivation may be amplified in females with loss of mosaicism in certain tissues or cell populations as well as in individuals with X aneuploidy, e.g. Kleinefelter patients, wherein all but one of the X chromosomes are inactivated 145 . Because the female bias is not uniform in all autoimmune diseases, it will be of interest to determine the underlying pathogenic processes that influence this bias, and to elucidate why males appear to require a higher cumulative genetic risk for disease development 146 .…”
Section: Gender Bias In Autoimmunitymentioning
confidence: 99%
“…The effect of incomplete X inactivation may be amplified in females with loss of mosaicism in certain tissues or cell populations as well as in individuals with X aneuploidy, e.g. Kleinefelter patients, wherein all but one of the X chromosomes are inactivated 145 . Because the female bias is not uniform in all autoimmune diseases, it will be of interest to determine the underlying pathogenic processes that influence this bias, and to elucidate why males appear to require a higher cumulative genetic risk for disease development 146 .…”
Section: Gender Bias In Autoimmunitymentioning
confidence: 99%
“…Another national Danish cohort‐based study ( n = 798) focused on autoimmune disease confirmed a doubling of the overall risk, and an increased prevalence of Hashimoto thyroiditis and T1D (Jorgensen et al, ). This increased risk of autoimmunity in Turner syndrome remains an enigma and is also present in another sex chromosome abnormality, Klinefelter syndrome (47,XXY) (Bojesen, Juul, Birkebaek, & Gravholt, ; Harris et al, ; Seminog, Seminog, Yeates, & Goldacre, ). The overall cancer risk in Turner Syndrome does not seem to be increased in comparison to the general female population (Gravholt et al, ; Schoemaker, Swerdlow, Higgins, Wright, & Jacobs, ).…”
Section: Epidemiologymentioning
confidence: 99%
“…We found excess 47,XXX and 47,XXY in patients with SLE or SS, but not in those with primary biliary cirrhosis or RA . Thus, we conclude that there is more than one path to sex bias in autoimmunity.…”
mentioning
confidence: 46%